A treasury of nursery rhymes (North Parade Pub. Bath, 2012)
"A Treasury of Nursery Rhymes" is a delightful collection of classic nursery rhymes and poems for young children. Featuring beloved favorites like "Twinkle, Twinkle, Little Star" and "Humpty Dumpty," the book is beautifully illustrated, making it visually appealing. It's designed to entertain and educate, promoting language development and rhythm while fostering a love for poetry in early learners.